The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13040785
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity and Functionality of Approved Human Immune Checkpoint Blockers in Dogs

Abstract: Background: Rodent cancer models have limitations in predicting efficacy, tolerability and accompanying biomarkers of ICIs in humans. Companion dogs suffering from neoplastic diseases have gained attention as a highly relevant translational disease model. Despite successful reports of PD-1/PD-L1 blockade in dogs, no compounds are available for veterinary medicine. Methods: Here, we assessed suitability of seven FDA-approved human ICIs to target CTLA-4 or PD-1/PD-L1 in dogs. Cross-reactivity and blocking potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Most canine tumors express PD-L1 constitutively and both innate and adaptive immune stimuli can further upregulate PD-L1 expression. 47 48 We expect that combining in situ eCPMV immunotherapy with crossfunctional human anti-PD-L1 inhibitors 49 or canine anti-PD-1/PD-L1 inhibitors, as they become available, 48 50 will result in higher efficacy than single agent used as monotherapy. We have demonstrated that in situ eCPMV synergizes with systemic checkpoint immunotherapy in various mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Most canine tumors express PD-L1 constitutively and both innate and adaptive immune stimuli can further upregulate PD-L1 expression. 47 48 We expect that combining in situ eCPMV immunotherapy with crossfunctional human anti-PD-L1 inhibitors 49 or canine anti-PD-1/PD-L1 inhibitors, as they become available, 48 50 will result in higher efficacy than single agent used as monotherapy. We have demonstrated that in situ eCPMV synergizes with systemic checkpoint immunotherapy in various mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of these checkpoint molecules has also been reported by our laboratory as increased in melanoma when compared with its benign counterpart melanocytoma and is associated with the density of CD3+ TILs (139). Recently, a group tested the cross-reactivity of different FDA-approved human immune checkpoint inhibitors (ICI) in canine tissue, showing two anti PD-L1 (Atezolizumab and Avelumab) with cross-reactivity, and Atezolizumab with the most robust T-cell cytokine production in vitro (140). A schematic representation of the immunotherapies in canine cancers is shown in Figure 3B.…”
Section: Current Immunotherapies In Dog Cancermentioning
confidence: 79%
“…Therefore, H77B-drug conjugate is one more option to treat dHER2-positive CMT. Recently, FDA-approved human immune checkpoint inhibitor against PD-1 and PD-L1 are used in canine tumor treatment (72)(73)(74); the combination of immune checkpoint inhibitors with other antibody-drugs is expected to be more effective. H77Bf could contribute to the development of canine cancer treatment, which can be feedback for human cancer treatment.…”
Section: Discussionmentioning
confidence: 99%